Decellularized nucleus pulposus matrix/chitosan hybrid hydrogel combined with nucleus pulposus stem cells and GDF5-loaded microspheres for intervertebral disc degeneration prevention - Tao Ma; Chen Liu; Quanlai Zhao; Yu Zhang; Liang Xiao (BMC, 2024)
Abstract Background Intervertebral disc degeneration (IDD) is considered an important pathological basis for spinal degenerative diseases. Tissue engineering is a powerful therapeutic strategy that can effectively restore the normal biological properties of disc units. In this study, hydrogels loaded with growth/differentiation factor 5 (GDF5) and stem cells were combined to provide an effective strategy for nucleus pulposus regeneration. Methods Nucleus pulposus stem cells (NPSCs) were obtained by low-density inoculation and culture, and their stem cell characteristics were verified by flow cytometry and a tri-lineage-induced differentiation experiment. A decellularized nucleus pulposus matrix (DNPM) and chitosan hybrid hydrogel was prepared, and GDF5-loaded poly(lactic-co-glycolic acid) (PLGA) microspheres were incorporated into the hydrogels to obtain a composite hydrogels with GDF5-loaded microspheres. Taking bone marrow mesenchymal stem cells (BMSCs) as a reference, the effect of composite hydrogels with GDF5-loaded microspheres on the chondrogenic differentiation of NPSCs was evaluated. A model of intervertebral disc degeneration induced by acupuncture on the tail of rats was constructed, and the repair effect of composite hydrogels with GDF5-loaded microspheres combined with NPSCs on IDD was observed. Results Stem cell phenotype identification, stemness gene expression and tri-lineage-induced differentiation confirmed that NPSCs had characteristics similar to those of BMSCs. The rat DNPM and chitosan hybrid hydrogels had good mechanical properties, and the GDF5-loaded microspheres sustainably released GDF5. NPSCs grew normally in the composite hydrogels and gradually expressed a chondrocyte phenotype. Animal experiments showed that the composite hydrogels with GDF5-loaded microspheres combined with NPSCs effectively promoted nucleus pulposus regeneration and that the effect of the hydrogels on the repair of IDD was significantly better than that of BMSCs. Conclusion GDF5-loaded microspheres combined with DNPM/chitosan composite hydrogels can effectively promote the differentiation of NPSCs into nucleus pulposus-like cells and effectively preventIDD.